2012
DOI: 10.1017/s1751731112000122
|View full text |Cite
|
Sign up to set email alerts
|

Grain source and marginal changes in forage particle size modulate digestive processes and nutrient intake of dairy cows

Abstract: This study investigated the effects of, and interactions between, dietary grain source and marginal changes in alfalfa hay (AH) particle size (PS) on digestive processes of dairy cows. A total of eight Holstein dairy cows (175 days in milk) were allocated in a replicated 4 3 4 Latin square design with four 21-day periods. The experiment was a 2 3 2 factorial arrangement with two levels of theoretical PS of AH (fine 5 15 mm or long 5 30 mm) each combined with two different sources of cereal grains (barley grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
36
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 35 publications
(50 reference statements)
9
36
4
Order By: Relevance
“…To reduce particle length of forage, cows can either increase time spent eating and ruminating, increase rate of chewing or both (Yang and Beauchemin, 2006). In the present study, minutes per kg of DMI for eating, ruminating and TC are greater than those observed by Kononoff and Heinrichs (2003), Teimouri Yansari et al (2004) and Nasrollahi et al (2012). Greater minutes per kg of DMI of eating, ruminating and TC gives cows an opportunity to reduce particle length by increasing chewing rate as diet particle length increases, rather than needing to increase time spent ruminating.…”
contrasting
confidence: 64%
See 4 more Smart Citations
“…To reduce particle length of forage, cows can either increase time spent eating and ruminating, increase rate of chewing or both (Yang and Beauchemin, 2006). In the present study, minutes per kg of DMI for eating, ruminating and TC are greater than those observed by Kononoff and Heinrichs (2003), Teimouri Yansari et al (2004) and Nasrollahi et al (2012). Greater minutes per kg of DMI of eating, ruminating and TC gives cows an opportunity to reduce particle length by increasing chewing rate as diet particle length increases, rather than needing to increase time spent ruminating.…”
contrasting
confidence: 64%
“…Kononoff and Heinrichs (2003) and Teimouri Yansari et al (2004) using lactating cows observed a linear increase in eating time per day and minutes per kg of DMI and NDFI as (alfalfa haylage in the first study and alfalfa hay in the second) particle length increased. Nasrollahi et al (2012) also observed an increase of the same variables for greater alfalfa hay particle length, whereas Yang and Beauchemin (2006) observed no differences when barley silage particle length increased. In the current study, no differences in total ruminating or TC minutes per kg of DMI or NDFI were observed, whereas Teimouri Yansari et al (2004) observed a linear increase of the same Mean length of particles retained on the top screen of the ASABE particle size separator.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations